Capillary electrophoresis as a technique to analyze sequence-induced anomalously migrating DNA fragments. - Wenz, H M (1994)
Sequence-induced anomalous migration of double-stranded (ds) DNA in native gel electrophoresis is a well known phenomenon. The retardation of migration is more obvious in polyacrylamide compared with agarose gels, and is greatly affected by the concentration of the gel and the temperature. This anomalous migration results in a difference between calculated and actual sizes of the affected DNA fragments. A low viscosity polymer solution (DNA Fragment Analysis Reagent) under investigation for use in dsDNA analysis by capillary electrophoresis is shown to be useful for the visualization of anomalies in migration of dsDNA fragments. Comparable with traditional slab gel systems, the retardation effect, indicative of bent or curved DNA, is strongly dependent on polymer concentration and separation temperature. These dependencies have implications on the accurate sizing of dsDNA fragments with unknown sequences and secondary structures.